2018
DOI: 10.3389/fpls.2018.00926
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study for Spot Blotch Resistance in Hard Winter Wheat

Abstract: Spot blotch (SB) caused by Cochliobolus sativus (anamorph: Bipolaris sorokiniana) is an economically important disease of wheat worldwide. Under a severe epidemic condition, the disease can cause yield losses up to 70%. Previous approaches like bi-parental mapping for identifying SB resistant genes/QTLs exploited only a limited portion of the available genetic diversity with a lower capacity to detect polygenic traits, and had a lower marker density. In this study, we performed genome-wide association study (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 107 publications
12
66
0
Order By: Relevance
“…were consistent with the results of [30]. Similarly, four chromosome regions on 1B, 3B, 4B and 5B are validating the finding of [21] which were based on testing in the field condition.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…were consistent with the results of [30]. Similarly, four chromosome regions on 1B, 3B, 4B and 5B are validating the finding of [21] which were based on testing in the field condition.…”
Section: Discussionsupporting
confidence: 89%
“…The nearly continuous distribution of lines in all the environments show quantitative nature of resistance. The same has been supported by earlier findings where more than two genes [35,12,13,36,37] and multiple alleles with minor effect [30,21] to control spot blotch resistance is reported. It was found that the log transformation improved the data normality which was also reflected by the improved consistency in the GWAS results across locations.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations